A novel technique for detecting antibiotic-resistant typhoid from rapid diagnostic tests. - Fhogartaigh, C; Dance, D; Davong, V; Tann, P; Phetsouvanh, R; Turner, P; Dittrich, S; Newton, P (American Society of Microbiology, 2015)
Fluoroquinolone-resistant typhoid is increasing. An antigen-detecting rapid diagnostic test (RDT) can rapidly diagnose typhoid from blood cultures. A simple, inexpensive molecular technique performed with DNA from positive RDTs accurately identified gyrA mutations consistent with phenotypic susceptibility testing results. Field diagnosis combined with centralized molecular resistance testing could improve typhoid management and surveillance in low-resource settings.